The incidence of PAX6 mutation in patients with simple aniridia: an evaluation of mutation detection in 12 cases. Issue 4 (April 1997) - Axton, R; Hanson, I; Danes, S; Sellar, G; van Heyningen, V; Prosser, J
Abstract : Twelve aniridia patients, five with a family history and seven presumed to be sporadic, were exhaustively screened in order to test what proportion of people with aniridia, uncomplicated by associated anomalies, carry mutations in the human PAX6 gene. Mutations were detected in 90% of the cases. Three mutation detection techniques were used to determine if one method was superior for this gene. The protein truncation test (PTT) was used on RT-PCR products, SSCP on genomic PCR amplifications, and chemical cleavage of mismatch on both RT-PCR and genomic amplifications. For RT-PCR products, only the translated portion of the gene was screened. On genomic products exons 1 to 13 (including 740 bp of the 3' untranslated sequence and all intron/exon boundaries) were screened, as was a neuroretina specific enhancer in intron 4. Ten of the possible 12 mutations in the five familial cases and five of the sporadic patients were found, all of which conformed to a functional outcome of haploinsufficiency. Five were splice site mutations (one in the donor site of intron 4, two in the donor site of intron 6, one in each of the acceptor sites of introns 8 and 9) and five were nonsense mutations in exons 8, 9, 10, 11, and 12. SSCP analysis of individually amplified exons, with which nine of the 10 mutations were seen, was the most useful detection method for PAX6.